Peningkatan Mutu Pendidikan Sebagai Upaya Kepala Sekolah dalam Memaksimalkan Fungsi Sebagai Supervisi di MTs 1 Kediri - Sunardi Sunardi; Khozainil Fauza (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2021)
The quality of education in Indonesia in general is still far from what was expected, the 2018 PISA score for Indonesia is ranked 72nd among 77 countries. The quality of education is identical to the maximum processed output. At MTs Negeri 1 Kediri in 2019, one of its students received the highest UNBK scores for SMP and MTs in Kediri Regency. The principal is one of the important factors in improving the quality of education in his school and one of the competences of the principal is as a supervisor. The problems studied were the principal's efforts to improve the quality of education, and the principal's techniques in carrying out supervision in an effort to improve the quality of education at MTs Negeri 1 Kediri. This research is a qualitative research. Data collection techniques using interviews, observation, and documentation. The data validity test used was to increase the persistence of observations and data triangulation. Data analysis techniques are data reduction, data presentation and conclusion. The results of the research, the efforts made by the principal included the formulation of a madrasah vision and mission, a solid team, developing the knowledge of educators, integrating curriculum, facilitating student interests and talents, realization of literacy programs, and maximizing information technology. While the techniques used in improving the quality of education include individual supervision techniques in the form of class visits and observations, individual meetings, and self-assessment. Also group supervision techniques in the form of teacher orientation, teacher meetings, discussions, workshops, exchange of experiences.